KEMAMPUAN MENEMUKAN IDE POKOK DALAM TEKS BERITA MELALUI MEMBACA SKIMMING SISWA KELAS VIII MTSN TALAOK KECAMATAN BAYANG PESISIR SELATAN - Sonela, Feby; Nisja, Indriani; Adrias, Adrias (Pendidikan Bahasa Indonesia, 2013)
The background of this research was studentsâ ability of MTsN Talaok to find the main idea of the new text was not maximized. The problem above because studentsâ interest in reading was low, studentsâ knowledge about main idea and write of main idea was not maximized. The teachersâ variety in teach still minimal. So the students bored to follow of study. Purpose of the research was to describe the ability of find out the main idea in news text through skimming reading at grade VIII Of students MTsN Talaok Bayang Sub South Coast.Â Â Â Â Â Â Â Â Â Â Â  This research used Agustinaâs (2008) opinion that theory about understanding of reading, the purpose of reading, type of reading, and find of main idea. The design of the research was quantitative with describe that ability of find out the main idea in news text through skimming reading at grade VIII Of students MTsN Talaok consist of. 1 student got very good. 7 students got good. 7 students got more than sufficient. 2 students got sufficient. 6 students got nearly enough. 2 students got least. 4 students got poor. 1 students got bad. The conclusion of this research to describe the ability of find out the main idea in news through skimming reading at grade VIII of students MTsN Talaok was not achieve maximum because value of average was 59,8 with level in the range 56â65%